The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1159/000241269
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Hydroxylase Activity and Catecholamine Content in the Adrenals of Young Hypo- and Hyperthyroid Rats

Abstract: The weight, the tyrosine hydroxylase (TH) activity and the catecholamine (noradrenaline and adrenaline) content of young rat adrenals have been measured from birth to 20 days after birth in relation to hypo- and hyperthyroidism. Hypothyroidism impairs the adrenal growth, while hyperthyroidism has no effect on the adrenal weight. Hypothyroidism is associated with an enhancement of TH activity and catecholamine content. In hyperthyroid rats, the increase in TH activity and catecholamine content is slower than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…It may be suggested that the increase in adrenal DA content is the consequence of tyrosine hydroxylase activation (Almgren et al, 1979; Snider and Kuchel, 1983). This suggestion was supported by the findings of other investigators who reported that the adrenal content of catecholamine and the activity of tyrosine hydroxylase and dopamine‐β‐hydroxylase, two enzymes involved in catecholamine biosynthesis, are modulated by the thyroid hormones (Gripois et al, 1980; Gripois and Valens, 1983).…”
Section: Discussionsupporting
confidence: 70%
“…It may be suggested that the increase in adrenal DA content is the consequence of tyrosine hydroxylase activation (Almgren et al, 1979; Snider and Kuchel, 1983). This suggestion was supported by the findings of other investigators who reported that the adrenal content of catecholamine and the activity of tyrosine hydroxylase and dopamine‐β‐hydroxylase, two enzymes involved in catecholamine biosynthesis, are modulated by the thyroid hormones (Gripois et al, 1980; Gripois and Valens, 1983).…”
Section: Discussionsupporting
confidence: 70%
“…These are the conditions we chose for the incubation in the present study. Even in these conditions, which do not correspond to the optimal functioning of the enzyme, the basal levels of tyrosine hydroxylase (as represented by the values for the saline-injected pups) are increased by neonatal hypothyroidism, just as they are when tyrosine hydroxylase is assayed under more optimal conditions (Gripois et al 1980;Lau & Slotkin 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the young rat, PNMT is modulated by hypo-and hyperthyroidism with TH and DBH [7,8,13,14] but to a lesser extent.…”
Section: Discussionmentioning
confidence: 99%